Non-Intubated Versus Intubated Video-Assisted Thoracic Surgery in Patients Aged 75 Years and Older: A Propensity Matching Study - Chen, Pei-Hsing; Chuang, Jen-Hao; Lu, Tzu-Pin; Hung, Wan-Ting; Liao, Hsien-Chi; Tsai, Tung-Ming; Lin, Mong-Wei; Chen, Ke-Cheng; Hsu, Hsao-Hsun; Chen, Jin-Shing (Frontiers in Surgery, 2022)
Introduction: In most developed countries, lung cancer is associated with the highest mortality rate among all cancers. The number of elderly patients with lung cancer is increasing, reflecting the global increase in aging population. Patients with impaired lung or cardiac function are at a high risk during intubated general anesthesia, which may preclude them from surgical lung cancer treatment. We evaluated the safety and survival of non-intubated video-assisted thoracoscopic surgery (VATS) versus those of intubated thoracoscopic surgery for surgical resection for lung cancer in older patients. Methods: Patients aged ≥75 years who underwent non-intubated and intubated VATS resection with pathologically confirmed non-small cell lung cancer, using a combination of thoracic epidural anesthesia or intercostal nerve block and intra-thoracic vagal block with target-controlled sedation, from January 2011 to December 2019 were included. Ultimately, 79 non-intubated patients were matched to 158 patients based on age, sex, body mass index, family history, comorbidity index, pulmonary function (forced expiratory volume in one second/ forced vital capacity[%]), and disease stage. The endpoints were overall survival and recurrence progression survival. Results: All patients had malignant lung lesions. Data regarding conversion data and the postoperative result were collected. Both groups had comparable preoperative demographic and cancer staging profiles. The anesthetic duration in the non-intubated group was shorter than that in the intubated group, which showed a significantly higher mean number of lymph nodes harvested (intubated vs non-intubated, 8.3 vs. 6.4) and lymph stations dissected (3.0 vs. 2.6). Intensive care unit (ICU) admission rate and postoperative ICU stay were significantly longer in the intubated group. The complication rate was higher and hospital stay were longer in the intubated group, but these differences were not significant (12% vs. 7.6%; p=.07, respectively). Conclusions: In the elderly, non-intubated thoracoscopic surgery provides similar survival results as the intubated approach, although fewer lymph nodes are harvested. Non-intubated surgery may serve as an alternative to intubated general anesthesia in managing lung cancer in carefully selected elderly patients with a high risk of impaired pulmonary and cardiac function.